MODEL EKONOMI KREATIF BERBASIS LOCAL ECONOMIC WISDOM PADA UMKM PEREMPUAN DI DESA RUKMA JAYA - Jumardi Budiman; Heni Kuswanti; Herkulana Herkulana (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
obstacles faced by women’s MSMEs in Rukmajaya Village, Sungai Raya Kepualauan District, Bengkayang Regency. The purpose of this study was to formulate a model for developing a creative economy based on local wisdom in order to increase the capacity of MSME practitioners. The method used was Research and Development (R & D). The respondents of this study were the Head of the Department of Labor and Transmigration, SMEs, and Cooperatives in Bengkayang Regency, the Head of Rukmajaya Village and the members of the woman organization (PKK) in Rukmajaya Village that had small businesses. The data analysis techniques used were data reduction, data display and drawing conclusion. The results showed several potential businesses developments in Rukmajaya Village, including a strategic location, the existence of an international port, the availability of raw materials and support from the government. The challenges faced were products marketing, additional capital, human resources, and managerial. Based on the study of the potentials and challenges, the researchers formulated the Pentahelix model which consists of five elements: 1) government; 2) academics; 3) MSMEs practitioners; 4) financial institutions; and 5) media